Lateralized organization of the cerebellum in a silent verbal fluency task: a functional magnetic resonance imaging study in healthy volunteers - Hubrich-Ungureanu, Petra; Kämmerer, Nina; Henn, Fritz A.; Braus, Dieter F. (Neuroscience letters, 2002)
Functionally, the cerebellum is not only involved in motor control but is also thought to influence higher cognitive function including language. Anatomical data would suggest crossed reciprocal connections between the cerebellum and higher order cortical association areas. In the following study, one left- and one right-handed female volunteer underwent functional magnetic resonance imaging in a conventional block design. Regions of activation were detected after performance of a silent verbal fluency task inside the scanner. In the right-handed volunteer we found an activation of the left fronto-parietal cortex and the right cerebellar hemisphere, while in the left-handed volunteer the activation was seen in the right fronto-parieto-temporal cortex and the left cerebellar hemisphere. These initial results demonstrate that cerebellar activation is contralateral to the activation of the frontal cortex even under conditions of different language dominance. They provide evidence for the hypothesis of a lateralized organization of the cerebellum crossed to the cerebral hemispheres in supporting higher cognitive function.
Gesehen am 09.11.2020